Evaluating the implementation of Bantuan Operasional Sekolah in vocational high schools of tourism in Indonesia - Felestin Felestin; Pardjono Pardjono; Zamroni Zamroni (Psychology, Evaluation, and Technology in Educational Research, 2022)
This study aims to reveal the implementation of BOS in Indonesia. This study used the evaluative-quantitative methods approach with the descriptive analysis. The results of the research are as follows; the context of the implementation is in category ineffective, the input of the implementation of the BOS program was in category effective, the process of the implementation of BOS has been running in category ineffective, and the number of respondents showing disagreement is more than agreement that means the implementation of BOS program was level ineffective. Fifth, there is an ineffective level of satisfaction.